Investigating two-stage degradation of threshold voltage induced by off-state stress in AlGaN/GaN HEMTs. (7th January 2022) - Lin, Yu-Shan; Chen, Yi-Lin; Chang, Ting-Chang; Ciou, Fong-Min; Zhu, Qing; Tai, Mao‐Chou; Su, Wan-Ching; Kuo, Ting-Tzu; Chen, Kuan-Hsu; Zhu, Jie-Jie; Mi, Min-Han; Ma, Xiao-Hua; et al.
Abstract: In this work, a two-step degradation phenomenon in D-mode Si3 N4 /AlGaN/GaN metal–insulator–semiconductor-high electron mobility transistors is discussed systematically. During off-state stress, threshold voltage shifts positively for a short duration, and is followed by a negative shift. In contrast, the off-state leakage continues to decrease throughout the entire stress. Results of varied measurement conditions indicate that carrier trapping at different regions dominates this phenomenon. It is interesting that under a large lateral electric field, electron–hole pairs are generated and will then be trapped at the gate dielectric layer. Furthermore, when increasing the stress temperature, impact ionization due to carriers from the gate electrode becomes more severe. Finally, devices with different gate insulator thicknesses are performed to verify the physical model of the degradation behavior.